Milo stover and forage sorghum silages for growing heifers - Bolsen, K.; Corah, L.; Grimes, C.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Ninety-six heifer calves were used to compare four silage combinations: (1) 100% milo stover, (2) 67% milo stover and 33% forage sorghum, (3) 33% milo stover and 67% forage sorghum and (4) 100% forage sorghum. Each ration was fed to four pens of six heifers each during the 88-day trial. Heifers fed 100% forage sorghum made the fastest and most efficient gains(P<.05); those fed 100% milo stover, the slowest and least efficient gains (P<.05). Based on gains obtained from these two rations, the 67% milo stover silage ration produced 16% faster gain than predicted; the 33% milo stover ration, a 5% faster gain than predicted.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Milo stover silage; Forage sorghum silage; Heifers